2016
DOI: 10.11114/jets.v4i12.1965
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Montessori Method Supported by Social Skills Training Program on Turkish Kindergarten Children’s Skills of Understanding Feelings and Social Problem Solving

Abstract: The current research was conducted with the purpose of analyzing the effect of Montessori method supported by Social Skills Training Program on kindergarten children's skills of understanding feelings and social problem solving. 53 children attending İhsan Doğramacı Applied Nursery School affiliated to Selcuk University, Faculty of Health Sciences in Konya during 2013-2014 school year were included in the study group. Wally Feelings Test and Wally Social Problem Solving Test were used as data collection tools.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
0
4
0
4
Order By: Relevance
“…A recent study of 3rd grade test scores in South Carolina found significantly higher standardized test scores for over 7000 children in 45 public Montessori schools (with varying quality of implementation) versus controls (Culclasure et al 2018). Other recent studies also show that Montessori-especially when it is implemented with high fidelity, but sometimes even when it is not-has strong outcomes in social emotional and academic realms (e.g., Ansari and Winsler 2014;Bhatia et al 2015;Brown and Steele 2015;Franc and Subotic 2015;İman et al 2017;Kayılı 2018;Kayılı and Arı 2016;Mix et al 2017;Pate et al 2014;Peng and Md-Yunus 2014;Stewart et al 2007). Montessori also fares better than other schools in terms of racial equality.…”
Section: Empirical Evidence On Montessori Outcomesmentioning
confidence: 97%
“…A recent study of 3rd grade test scores in South Carolina found significantly higher standardized test scores for over 7000 children in 45 public Montessori schools (with varying quality of implementation) versus controls (Culclasure et al 2018). Other recent studies also show that Montessori-especially when it is implemented with high fidelity, but sometimes even when it is not-has strong outcomes in social emotional and academic realms (e.g., Ansari and Winsler 2014;Bhatia et al 2015;Brown and Steele 2015;Franc and Subotic 2015;İman et al 2017;Kayılı 2018;Kayılı and Arı 2016;Mix et al 2017;Pate et al 2014;Peng and Md-Yunus 2014;Stewart et al 2007). Montessori also fares better than other schools in terms of racial equality.…”
Section: Empirical Evidence On Montessori Outcomesmentioning
confidence: 97%
“…Óvodáskorban a szociálisprobléma-megoldás jelentős fejlődésen megy keresztül, amit a személyiségbeli, öröklött és tanult tényezők együttesen határoznak meg (Kasik & Gál, 2014a;Walker et al, 2013). Kutatások (Frauenknecht & Black, 2009;Strough & Keener, 2014) alátámasztják, hogy az életkor előrehaladtával, így az óvodai évek alatt is a szociálisprobléma-megoldás egyre tudatosabbá válik, amit a kognitív jellemzők, a társas tapasztalatok, az elsajátított normák és szabályok együttesen befolyásolnak (Gál & Kasik, 2015;Kasik & Gál, 2017a;Kayili & Ari, 2016).…”
Section: óVodások Szociálisprobléma-megoldásaunclassified
“…A 13 problémahelyzet képekkel való ismertetése után arra a kérdésre kell válaszolniuk a gyerekeknek, hogy hogyan oldanák meg azt a helyzetet (Schell et al, 2015). A gyermekek által adott megoldási lehetőségeket három főkategóriába (pozitív, negatív, semleges) sorolták (Kayili & Ari, 2016;Overdorf, 2014). Webster-Stratton és Lindsay (1999) e mérőeszközzel végzett kutatásában 4-7 éves viselkedészavarral küzdő gyermekek és átlagosan fejlődő gyermekek vettek részt.…”
Section: Táblázat óVodásokunclassified
“…al., 2015;Özbey & Köyceğiz, 2019;Uysal, & Kaya-Balkan, 2015). In studies based on social skills training on preschool children, it was revealed that social skills training is effective in the development of children's skills of understanding feelings and social problem solving, social competencies, peer relations, self-esteem, social behaviors, positive play behaviors, and motivation levels (Bilir-Seyhan, Ocak-Karabay, Arda-Tunçdemir, Greenberg & Domitrovich, 2017;Dereli, 2009;Hwa-Choi, & Md-Yunus, 2011;Kaya & Deniz, 2020;Kayılı & Arı, 2016;Larose et. al., 2020;Özbey & Köyceğiz, 2019;Özdemir-Topaloğlu, 2013;Sancak, 2019;Uysal, & Kaya-Balkan, 2015).…”
Section: Introductionmentioning
confidence: 99%